Nontuberculosis mycobacterial infections at a specialized tuberculosis treatment centre in the Republic of Korea - Hee Jung Yoon; Hwa Young Choi; Moran Ki (BMC Infectious Diseases, 2017)
Abstract Background The incidence of nontuberculous mycobacteria (NTM) infections is increasing worldwide, however formal evaluations of the epidemiology of NTM infections are limited. Understanding the trends and true prevalence of NTM is a major priority for optimizing infection control programmes and resources. The purpose of this study was to investigate the epidemiology, clinical manifestations, and radiologic findings in NTM-infected patients at specialized Tuberculosis (Tb) treatment centre in South Korea, which is endemic to Tb, and find solutions to control NTM infections. Methods A retrospective descriptive study was conducted among patients who were diagnosed with NTM from November 2011 to January 2016 at Seoul Metropolitan Government Seobuk hospital, Korea, using medical records and chest radiography results. Prevalence of NTM using national health insurance data was compared to the prevalence and incidence of Tb using National statistics data. Results The age- and sex- adjusted prevalence of NTM infection per 100,000 population increased between 2009 (9.4) and 2016 (36.1). However, the prevalence and incidence of Tb per 100,000 population decreased from 106.5 to 74.4, and 81.2 to 61.8, respectively. In total, 64 patients (37 [57.8%] men) were enrolled in the study. Among 33 (51.6%) patients with slowly growing nontuberculous mycobacteria (SGM) infection, 29 were detected with Mycobacterium avium complex (n = 13, M. avium; n = 16, M. intracellulare), and 4 with M. kansasii. Among 31 (48.4%) patients with rapidly growing nontuberculous mycobacteria (RGM) infection, 27 and 4 patients were detected with M. abscessus complex and M. fortuitum complex, respectively. RGM patients were more likely to have current Tb (P = 0.041), cough (P < 0.05), and sputum (P < 0.01) than SGM patients in the univariate analysis, but not in the multivariate analysis. Conclusion Given the increasing prevalence of NTM infections, precise epidemiological and surveillance data should be obtained by reporting NTM infections to public health authorities. Introducing nucleic acid amplification tests to differentiate between Tb and NTM in smear-positive specimens should be considered.